Educational Values in Surah Luqman: A Perspective from Al-Maraghi's Tafsir - Annibras, Nablur Rahman (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2024)
This study explores the educational values in Surah Luqman from the perspective of Al-Maraghi's Tafsir, aiming to identify and analyze the relevance of these values in modern life. Employing a qualitative approach with a library research method, the study integrates an analysis of Quranic text, tafsir literature, and related educational resources. The findings reveal five key educational values in Surah Luqman: monotheism (tauhid), morality (akhlaq), social responsibility, worship (ibadah), and environmental awareness. Al-Maraghi's Tafsir emphasizes the practical application of these values in shaping individual character and society. These findings address contemporary challenges such as moral crises, individualism, and environmental degradation. This research contributes theoretically by highlighting the relevance of Quranic values in modern education and advocating for their integration into curricula. However, the study is limited to Al-Maraghi's perspective, suggesting opportunities for comparative analysis with other tafsir works.